Self-system and Mental Health Status among Malaysian Youth Attending Higher Educational Institutions: A nationwide Cross-Sectional Study - Syifa’ Mohd Azlan; Fadzilah Mohamad; Rahima Dahlan; Irmi Zarina Ismail; Hayati Kadir@ Shahar; Khairatul Nainey Kamaruddin; Nur Amirah Shibraumalisi; Sharifah Najwa Syed Mohamad; Nurainul Hana Shamsuddin (Academy of Family Physicians of Malaysia and Family, 2024)
Indexed by Scopus